Hubungan Antara Konsep Diri dengan Kecemasan Sosial pada Mahasiswa Bandung - Pratiwi, Sekar Larasati; Ramdhani, Rina Nurhadi; Taufiq, Agus; Sudrajat, Dadang (IAIN Kudus, 2023)
The Relationship Between Self-Concept and Social Anxiety in Bandung Students. This study aims to determine the relationship between self-concept and social anxiety in college students. The population in this study were students in Bandung and the participants in this study totaling 35 respondents were taken using the accidental sampling technique and the scales used were self-concept scale and social anxiety scale. The correlation technique used to determine the relationship between self-concept and social anxiety variables is the Spearman Rho technique with the help of the IBS SPSS version 22.00 for windows computer program. The results of the study prove that there is a negative and significant relationship between self-concept and social anxiety in college students. By calculating the data analysis, it shows that the Spearman's Rho correlation coefficient is -0.745 with a significance value of 0.000 (p <0.01). This shows that the proposed hypothesis is accepted. That is, the higher the student's self-concept, the lower the social anxiety, and vice versa if students have a low self-concept, the higher the social anxiety. This research also supporting and justifying the previous theory and research between anxiety and self concept.Keywords: Self-Concept, Social Anxiety, and Students.